2014
DOI: 10.1007/s11250-014-0715-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and bacteriological investigation of subclinical mastitis caused by Staphylococcus aureus and Streptococcus agalactiae in domestic bovids from Ismailia, Egypt

Abstract: A study was carried out to establish the prevalence of subclinical mastitis (SCM) in smallholder dairy farms in Ismailia, Egypt. A total of 340 milking cows and buffaloes were sampled from 60 farms, and 50 nasal swabs were collected from consenting farm workers. Milk samples were subjected to California mastitis test (CMT) and the positive samples were examined by bacterial culture and PCR to identify etiological agents. Based on CMT, the prevalence of SCM was 71.6 % in cattle and 43.5 % in buffaloes while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 29 publications
6
20
1
1
Order By: Relevance
“…This was confirmed by the results of the molecular analysis that showed that most of the isolated strains were not S. aureus. SCM was also more prevalent than CM, which agrees with previous studies (Elhaig & Selim, 2015), and highlights the importance and widespread nature of SCM.…”
Section: Discussionsupporting
confidence: 91%
“…This was confirmed by the results of the molecular analysis that showed that most of the isolated strains were not S. aureus. SCM was also more prevalent than CM, which agrees with previous studies (Elhaig & Selim, 2015), and highlights the importance and widespread nature of SCM.…”
Section: Discussionsupporting
confidence: 91%
“…This was confirmed by PCR which showed that most of Staphylococcus isolates were not S. aureus. In addition, SCM was more prevalent than CM, which agrees with a recent study in Egypt (Elhaig & Selim, 2015), and highlights the importance and widespread nature of SCM.…”
Section: Discussionsupporting
confidence: 91%
“…Molecular epidemiology studies on MRSA in southern Mediterranean countries are limited (Borg et al, 2007). In Egypt, there are very few studies on MRSA strains originating from bovine mastitis (Elhaig and Selim, 2015). Additionally, studies de-scribing the clinical aspects of MRSA-and non-MR-SA-associated bovine mastitis are limited.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of herds infected with S. agalactiae varies worldwide. Although some countries have apparently managed to almost eradicate the pathogen (Bradley et al, 2007;Piepers et al, 2007), others, such as Egypt, Canada, Estonia, and Germany, report herd prevalences of 20, 9, 12, and 29%, respectively (Tenhagen et al, 2006;Kalmus et al, 2011;Francoz et al, 2012;Elhaig and Selim, 2015). Australian reports suggest that S. agalactiae is present in from 1 to 6% of herds in southeastern Australia (Penry et al, 2014).…”
Section: Introductionmentioning
confidence: 99%